Innovations in the Improvements of Soft Bangkok Clay using Prefabricated Vertical Drains and Deep Cement Mixing (DCM) - D.T Bergado; S Manandhar; S Soralump; T Hino (International Association of Lowland Technology, 2020)
Soft ground improvement techniques such as PrefabricatedVertical Drains (PVD) and Deep Cement Mixing (DCM) are themost practical and popular methods to increase soil strength, soilstiffness and reduce soil compressibility of soft clays. PVDs areartificial drainage paths to vertically drain the pore watersqueezed out from the soft clay due hydraulic gradient generatedby preloading. DCMs are piles formed by mixing cement with softclays. This paper focuses on innovations and comparativeperformances of PVDs using surcharge, vacuum and heatpreloading as well as the cement-admixed clay of DCMs andStiffened DCM (SDCM) methods for the improvement of softBangkok clays. The Vacuum-PVD can increase the horizontalcoefficient of consolidation, Ch, resulting in faster rate ofsettlement at the same magnitudes of settlement compared toConventional PVD. Moreover, the new methods of Thermal PVDand Thermal Vacuum PVD can increase further the coefficient ofhorizontal consolidation, Ch, with the associated reduction ofkh/ks values by reducing the drainage retardation effects in thesmear zone around the PVD which resulted in faster rates ofconsolidation and higher magnitudes of settlements. A new kindof reinforcing method, the SDCM pile consists of DCM pilereinforced with precast reinforced concrete (RC) core pile. Thesimulation results using PLAXIS 3D indicated that the surfacesettlements decreased with increasing lengths of the RC corepiles. In addition, the lateral movements of the embankmentdecreased by increasing the lengths (longer than 4 m) and, thesectional areas of the RC core pile